2016
DOI: 10.1016/j.actao.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Gone with the wind and the stream: Dispersal in the invasive species Ailanthus altissima

Abstract: a b s t r a c tDispersal is a key process in plant invasions and is strongly related to diaspore morphology. Often, dispersal comprises more than one step, and morphologies adapted to a primary dispersal mechanism can aid or detract from a secondary one. The aim of this work was to assess the relationship between primary wind dispersal and secondary water dispersal in Ailanthus altissima, an invasive tree species. Wind and water dispersal potential and their association with the morphological characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 44 publications
2
19
0
4
Order By: Relevance
“…Roads also act as a corridor utilized by livestock and wildlife, allowing them to freely move through the landscape. Livestock and wildlife can disperse seeds that are partly edible or that may be attached to them (Planchuelo et al 2016). As a result, livestock and wildlife could be potential vectors by which native invasive species spread.…”
Section: Discussionmentioning
confidence: 99%
“…Roads also act as a corridor utilized by livestock and wildlife, allowing them to freely move through the landscape. Livestock and wildlife can disperse seeds that are partly edible or that may be attached to them (Planchuelo et al 2016). As a result, livestock and wildlife could be potential vectors by which native invasive species spread.…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable variation in samara structure both among and within species as well as within individuals (Peroni, 1994;Sipe & Linnerooth, 1995). Although there has been some research done on how such variation affects the primary dispersal of samaras (Greene & Johnson, 1993;Sipe & Linnerooth, 1995;Delgado et al, 2009), there is little understanding of the impact of this variation on secondary dispersal, by any vector (Planchuelo et al, 2016). Intra-individual variation in samara shape and structure may be an evolutionary response to different dispersal vectors, and hence understanding the relationship between the samara structures and possible dispersal vectors could reveal the adaptations shown by individual plants.…”
Section: Future Researchmentioning
confidence: 99%
“…This could mean that selection would favour greater wing surface area, so that the flotation ability of the seed is improved (Säumel & Kowarik, 2013), or that the seed and wing separate faster in species that use animal as well as wind dispersal. For example, in Ailanthus altissima, samaras with slower descent velocities also have longer floating times in water (Planchuelo, Catalán & Delgado, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of such large-scale invasions in forests and their adverse effects on native species richness and incidence have only been recently elucidated [7][8][9][10]. Invasions of Ailanthus along transportation corridors have long been recognized, but only recently have studies assessed the mechanisms of spread in these environments [11][12][13]. Researchers are now beginning to appreciate the role that roads play in facilitating forest invasions [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Ailanthus is unexpectedly fecund even in environments presumably less favorable for invasion such as closed canopy forests [9,18] or as germinants following submergence in water [19,20]. Recent studies have shown certain morphological characteristics (e.g., samara width) affect water dispersal positively, but affect wind dispersal negatively [11].…”
Section: Introductionmentioning
confidence: 99%